Assistive Technology and Inclusion: a look at teaching practice with students with intellectual disabilities (Research, Society and Development, 2020)
This article aimed to identify which types of Assistive Technology are used to assist the learning of students with Intellectual Disabilities in schools. To this end, an investigation was developed with a qualitative and descriptive approach that used the questionnaire as a research technique. The research subjects were 31 student professors of the Lato sensu Graduate Program in Teaching, from the Federal Institute of Minas Gerais (IFMG) Campus Arcos. It was found that the Assistive Technologies most used in teaching practice with students with Intellectual Disabilities are those linked to Information and Communication Technologies with the use of computers and electronic instruments. However, it is also clear that teachers have little knowledge about Assistive Technology, presenting difficulties in relation to the lack of information on how to use it in their daily lives, difficulty in selecting in which learning situations Assistive Technology can be used. . And they still point out the lack of resources or their insufficiency at school as a hindrance to work. We conclude the need to implement continuous training for teachers on this topic, so that they can do an effective job with students with Intellectual Disabilities, seeking inclusion.